COVID-19 and Vaccination Campaigns as “Western Plots” in Pakistan: Government Policies, (Geo-)politics, Local Perceptions, and Beliefs - Ali, Inayat; Sadique, Salma; Ali, Shahbaz (Frontiers in Sociology, 2021)
Vaccination encounters multiple context-specific challenges—socio-cultural, economic, and political— that substantially affect its uptake. Likewise, natural disasters and health emergencies considerably impact immunization endeavors, such as the COVID-19 pandemic that has overwhelmed the entire world. It was already anticipated that the pandemic would severely affect Pakistan's vaccination programs due to interruptions in routine vaccination and the overstretching of healthcare systems. Consequently, there are anticipations of outbreaks of other vaccine-preventable diseases (VPDs). Yet empirical evidence is missing. Drawing on qualitative research, this article focuses on the impact of COVID-19 on routine vaccination programs in Pakistan. Our data come from a small village located in Pakistan’s Sindh province where local people refused the routine polio vaccine that was stopped for a while, then resumed in July 2020. They suspected both the vaccine and COVID-19 to be a “Western plot.” We argue that these perceptions and practices can be seen against the backdrop of economic, socio-cultural, and (geo)political forces, which are encoded in “societal memory.” Not only is there a need to reverse the significant impacts of COVID-19 on routine vaccination by arranging supplementary immunization activities (SIAs), but also the government must deal with other pressing issues that affect the vaccination programs in the country.